Long-term air quality trends of regulated pollutants in Helsinki metropolitan area in 1994-2019 and implications to air quality index - Sillanpää, Salla; Fung, P.L; Niemi, J.V.; Kousa, A; Kangas, L; Zaidan, M.A.; Timonen, H; Kulmala, M.; Petäjä, T; Hussein, T (Finnish Environment Institute, 2022)
Long-term trends of ambient gaseous pollutants and particulate matter in Helsinki metropolitan area were analyzed from 1994 to 2019. Measurement data from ten monitoring stations located in different types of urban environments including traffic, urban background, rural background, and suburban area were included in this study. We analyzed gas-phase air pollutants, such as NO, NO2, NOx, O3, SO2 and CO; and for aerosol pollutants, we explored mass concentrations for particles smaller than 10 µm and 2.5 µm in diameter (PM10 and PM2.5, respectively ). In order to quantify trends in the data, we deployed a non-parametric Mann-Kendall test and Theil-Sen method. The results were compared with the regional emissions trends and changes in meteorological conditions. Our analysis indicates that SO2 and CO in all stations have decreased to values corresponding to their regional background concentration levels and their role as urban air pollutants have diminished. Our results from the Helsinki Metropolitan area during the last 25 years show that the air quality improved and all the air pollutant concentrations show a decreasing trend, except ozone. Based on our analysis of the Air Quality Index (AQI) at traffic and urban background environments, NO2 concentration, which have typically represented the health effects resulting from vehicular traffic, is rapidly decreasing also in traffic environments. The current AQI standard therefore lacks clarity on the potential health risks from other air pollutants emitted from traffic exhaust. In addition, the air quality indicators currently considered in the AQI do not represent well enough residential wood burning and the possible health outcomes from its exposure. We suggest that the current AQI should be revised in a way that new air quality parameters would be considered, which would better represent the health effects resulting from these local combustion sources.